The Influence of Secondary Structures on Wear Resistance of Experimental Aluminum Alloys for Monometallic Slide Bearings. (2019) - Podrabinnik, Pavel; Mironov, Alexander; Gershman, Iosif
Abstract: The changes occurring on the surface of an experimental high-alloyed aluminum after friction with a steel counterbody have been investigated. The friction surface of the aluminum alloy has been studied by means of scanning electron microscopy and modification of elementary composition on it has been analyzed by energy-dispersive analysis. It has been revealed that secondary structures are formed on the surface during friction process and include all the chemical elements of the tribosystem which is a consequence of its self-organization. The influence of some chemical elements on tribotechnical characteristics of the alloy has been evaluated.